PERTANGGUNGJAWABAN PENGURUS YAYASAN TERHADAP PAILITNTA YAYASAN MENURUT UNDANG-UNDANG NO. 16 TAHUN 2001 SERTA PERUBAHANNYA (UNDANG-UNDANG NO. 28 TAHUN 2004 TENTANG YAYASAN) - EDDY PUTRA MELIALA; RAMLI SIREGAR; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
Fondation as a nonprofit institution, that is generally engaged in education, health, the field of religion, culture, and social areas. Fondation is a legal entity consisting of wealth separated and destined to achieve certain goals in the social, religious, and humanitarian who has no members. Fondations can establish a business entity whose activities are in accrordance with the intent and purpose of the foundation. How the establishment of the fondation, as well as the formation of necessity fondation has been set in the notarial dedd. So too has about organ foundation, namely builder, administrators, and supervisors. The issue in this skripsi is how to setup the foundation according to Law Number 16 Year 2001 Jo. Law Number 28 Year 2004 on the Foundation, how bankruptcy foundations, as well as how the board accountability to its foundations bankruptcy. The research method used type of normative legal research. Source of data used are secondary data, which consists of primary legal materials, secaondary, and tertiary. Data was collected by the engineering literature study and analysis of data using qualitative and inductive approach dedukatif. Setting the foundation under the Act include the establishment of the foundation that requires the establishment of the notarial deed of foundation, the foundation also set about organ consisting of supervisors, managers and supervisors. An experienced bankruptcy foundations can be caused by the foundation has two or more creditors and not pay in full at least one debt that has matured and can be billed, declared bankrupt by a court decision. Accountability board to bankrupt its foundation is as stipulated in Article 39 of Law Foundation is if bankruptcy occurred because of errors or omissions and intellectual foundation board is not enough to cover the losses caused by bankruptcy. Kata Kunci : Tanggung Jawab, Pengurus, Yayasan, Kepailitan